Anthracene‐Based Medium Bandgap Conjugated Polymers for High Performance Polymer Solar Cells Exceeding 8% PCE Without Additive and Annealing Process. Issue 11 (10th April 2015) - Jung, Jae Woong; Liu, Feng; Russell, Thomas P.; Jo, Won Ho
<x xml:space="preserve">Abstract</x> A series of medium bandgap polymers based on 9, 10‐thienylanthracene and benzothiadiazole are synthesized. The optical, electrochemical, intermolecular, and charge transport characteristics of the polymers are tuned by the introduction of various substituents. The fluorine‐substituted polymer exhibits much enhanced charge generation with reduced bimolecular recombination, thereby achieving a high power conversion efficiency exceeding 8%.